Urban environmental determinants of respiratory health: The role of air pollution, housing conditions, and green open space - Tuti Yelvianti; Muhammad Fachri; Nurmalia Lusida (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Rapid urbanization has increased exposure to multiple environmental stressors including air pollution, inadequate housing, and limited access to green open spaces, all of which adversely affect respiratory health. Understanding the interplay of these factors is essential for developing evidence-based urban health policies. Purpose: To synthesize evidence on the determinants of urban environments — specifically air pollution, housing conditions, and green open spaces — and their effects on respiratory health outcomes. Method: This study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. Literature searches were conducted using keywords "urban environment", "air pollution", "housing", "green space", and "respiratory health" across databases. A total of 15 articles published between 2022 and 2025 met the inclusion criteria. Results: Evidence consistently demonstrates that exposure to PM2.5, NO2, and traffic-related air pollutants is significantly associated with reduced lung function and increased incidence of asthma, COPD, and acute respiratory infections. Poor housing conditions — particularly overcrowding, dampness, and inadequate ventilation — exacerbate respiratory disease burden. Access to green open spaces was associated with protective respiratory effects. Conclusion: Urban environmental determinants collectively and interactively shape respiratory health. Integrated urban planning that reduces air pollution, improves housing standards, and expands green infrastructure is critical for respiratory health promotion in rapidly growing cities.